Structural Degradation of the Welded Joint of the Gas Main after a Long-Term Operation in Sub-Acid Soil; IOP Conference Series: Earth and Environmental Science; Vol. 115 : Ecology and safety in the technosphere - Maruschak P. O.; Bishchak R. T.; Maruschak O. V.; Panin S. V. Sergey Viktorovich (2018, 2018)
Title screen